Effectiveness of the Procurement and Distribution of Subsidized Fertilizers under Ministerial Regulation No. 4 of 2023 on Procurement and Distribution of Subsidized Fertilizers for the Agricultural Sector - Hasan Basri; Ade Saptomo (PT. Publikasiku Academic Solution, 2024)
This study investigates the dualism of roles within the Regional House of Representatives (DPRD) in Indonesia, focusing on its legislative and executive functions in the regional government system. As a legislative institution representing the people and a partner of the executive, the DPRD faces challenges in balancing these roles, often leading to potential conflicts of interest and weakened oversight functions. The study aims to analyze the challenges and propose strategies for enhancing the effectiveness of the DPRD in fulfilling its dual roles. Using a normative juridical approach, this research examines legislative provisions and conceptual frameworks to identify the gaps and complexities in the DPRD's current position. The findings reveal that role conflicts hinder the DPRD's ability to effectively oversee and collaborate with regional governments, affecting policy quality and public trust. This study recommends clear role delineation, enhanced institutional capacity, and improved communication between the DPRD and regional governments. These measures are expected to strengthen the DPRD’s legislative and oversight functions while maintaining its partnership with the executive, ultimately contributing to more effective and transparent regional governance.